Analisis Aksesibilitas Untuk Desain Yang Inklusif Bagi Difabel di Lapangan Blang Padang, Banda Aceh - Nadia Karmila; Muhammad Naufal Fadhil; Nurul Fakriah (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2025)
Blang Padang FieldBanda Acehis an urban green open space designated as a public area to accommodate diverse community activities. Its strategic location and high historical value attract many visitors. However, accessibility for persons with disabilities, particularly the visually impaired and those with mobility impairments, remains inadequate. These groups have equal needs and rights to utilize the public space. This study aims to formulate concepts for providing accessibility for visually impaired and mobility-impaired persons at Blang Padang Field. A qualitative method was employed through observation and documentation.